Design of a low-noise preamplifier for nerve cuff electrode recording. - Rieger, R. (IEEE Journal of solid state circuits)
This paper discusses certain important issues involved in the design of a nerve signal preamplifier for implantable neuroprostheses. Since the electroneurogram signal measured from cuff electrodes is typically on the order of 1 μV, a very low-noise interface is essential. We present the argument for the use of BiCMOS technology in this application and then describe the design and evaluation of a complete preamplifier fabricated in a 0.8-μm double-metal double-poly process. The preamplifier has a nominal voltage gain of 100, a bandwidth of 15 kHz, and a measured equivalent input-referred noise voltage spectral density of 3.3 nV/√Hz at 1 kHz. The total input-referred rms noise voltage in a bandwidth 1 Hz-10 kHz is 290 nV, the power consumption is 1.3 mW from ±2.5-V power supplies, and the active area is 0.3 mm2.